PERTUMBUHAN DAN DETEKSI GEN KETAHANAN TERHADAP Cucumber mosaic virus PADA JAGUNG HIBRIDA (Zea mays L.) HASIL PERSILANGAN KULTIVAR SRIKANDI KUNING-1 DENGAN GULUK-GULUK - , Pratanti Haksiwi Putri, Dr. Diah Rachmawati, M. Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Maize is one of the most important crops in the world. National income of maize reaches 9,4 trillion (2000) and increasing to 18,3 trillion (2003). The increase of productivity is projected will raises over year. Hybridâs maize has developed to increase the productivity. Pest and disease becomes one of the most influence problem of the aim. Cucumber mosaic virus (CMV) is a virus that has extensive host, up to more than 1200 specieses in 100 family, including maize. CMV causes decline of maize productivity. The local maize of Madura, Guluk guluk, known to have viruses resistency, including CMV and harvest earlier, meanwhile Srikandi Kuning-1, one of the Quality Maize's Protein (QPM), has higher protein content, but thereâs no information about itâs resistency to viruses yet. Hybridâs maize from them, named Gama GS and SG, known to have viruses resistency, harvest earlier and higher protein content. Resistance gene to CMV on the hybrid has analyzed by ELISA, but the detection to resistance gene to CMV haven't informed yet. The aim of this research are to detect resistance gene to CMV on hybridâs maize, and to analyzes itâs growth on different location. Seven commercial cultivar and 2 hybrid grown at 2 locations, with Randomized Complete Block Design, consist of 3 groups (replications), each comprise of 9 plots (cultivar) and planted out 80 plants each plot. Growth parameter, that is high and flowering age measured at the time of flowering, meanwhile, the productivity measured after harvesting. Resistance gene to CMV detected on kultivar Srikandi Kuning-1, Guluk guluk, Bisi 816, Pioneer 21, Gama GS and SG with Polymerase Chain Reaction (PCR). The result shows that Gama GS and SG flowering at the stage of 51-52 days, while the others at 55-63 days after planting. Both of them are not higher than the others in high and productivity. Resistance gene against CMV is not found, weither in Gama GS or Gama SG using MRGA-f1 that was used in Melon. For that, we guest maize has different resistance mechanism against CMV.